Path Analysis on the Effect of Healthy Behavior and other Determinants on Infant Mortality: Evidence from Karanganyar District, Central Java - Palupi, Endang; Salimo, Harsono; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: One indicator of a country’s progress is the infant mortality rate. Infant mortality is affected by many factors, both exogenous and endogenous. This study aimed to determine the factors causing significant infant mortality to reduce infant mortality in Karanganyar Regency. Subjects and Method: This study was an observational study with a cross-sectional design. This study was conducted in Karanganyar Regency from February to May 2020. The sample was 200 study subjects. The sample was selected by fixed disease sampling. The criteria were babies aged 1 month to fewer than 2 years. The variables observed for the effect were infant mortality, clean and healthy life behavior, exclusive breastfeeding, parental income, maternal education, infant nutritional intake, immunization status, birth weight of infants, illness history of infants, health services, cleanliness of the home environment. The data were collected by a set of questionnaires and analyzed using path analysis with Stata version 13. Results: The risk of infant mortality increased by the cleanliness of the home environment (b=3.84; 95%CI=1.76 to 5.92; p<0.001), infant nutrition intake (b=4.07; 95 CI=2.25 to 5.89; p<0.001), illness history of infants (b=3.03; 95%CI=1.34 to 4.72; p<0.001). The risk of infant mortality decreased by clean and healthy life behavior (b=-5.34; 95%CI=-7.75 to -2.94; p<0.001). Infant mortality was affected indirectly by exclusive breastfeeding, parental income, maternal education, birth weight of infants, immunization status, and health care facilities. Conclusion: Infant mortality is directly affected by the cleanliness of the home environment, clean and healthy life behavior, nutritional intake of infants, and illness history of infants. Infant mortality is indirectly affected by exclusive breastfeeding, parental income, maternal education, birth weight of infants, immunization status, and health care facilities. Keywords: Healthy behavior, determinant infant mortality, path analysis Journal of Maternal and Child Health (2020), 05(05): 467-481 https://doi.org/10.26911/thejmch.2020.05.05.02.